Intra‐annual rainfall variability in the Spanish hydrographic basins. (2nd November 2017) - García‐Barrón, L.; Aguilar‐Alba, M.; Morales, J.; Sousa, A.
ABSTRACT: Understanding the intra‐annual distribution of rainfall is an important element for climatic classification and serves as a basis for natural resources management. The present study analyses multi‐annual irregularities of the rainfall distribution throughout the year in the period 1941–2010, in the hydrographic basins of the Iberian Peninsula. In order to analyse its variation, the rainfall centralisation and dispersion parameters throughout the annual cycle were previously defined and calculated for each year. Inter‐annual series of both parameters were generated, which allowed detecting their temporal behaviour in each of the basins and relating differentiated geographic areas. Independent of the total annual rainfall, greater temporal simultaneity is observed in the fluctuations of the intra‐annual parameter 'centralisation' in the Atlantic basins and wider inter‐annual oscillations in the Mediterranean basins. Around the year 1970, there was a displacement in the predominance of autumn rains, although the process is inverted in the last decades. Also from the decade of 1970 there is a general increase in the inter‐annual variability of the 'dispersion' parameter, especially in the basins that drain towards the Atlantic Ocean. The 'dispersion' parameter allows detecting latitudinal (Cantabrian vs . Guadalquivir) and longitudinal (Atlantic vs . Mediterranean) patterns of intra‐annual rainfall distribution irregularity in the Iberian Peninsula. The results obtained are also associated to atmospheric general circulation patterns of the North Atlantic Oscillation and the Western Mediterranean Oscillation. The monthly winter values of the North Atlantic Oscillation present a marked influence on dispersion, especially in the basins that discharge into the Atlantic Ocean, which show a double gradient: decreasing longitudinally from the Atlantic coast to the Mediterranean coast and latitudinally from north to south. Abstract : The procedure applied in this article allowed for the precise quantification of the intra‐annual rainfall distribution for each year using centralisation Cn and dispersion Dn parameters. This made it possible to generate a temporal series for each basin and detect variability throughout the period observed (1941–2010). Furthermore, spatial relationships were established after comparing the behaviour of both parameters among the hydrographic basins.